(untitled) (Research, Society and Development, 2021)
To analyze the university students’ lifestyle of different shifts. It was instigated 400 students of a university in Paranavaí, 287 of Business and 113 of Pedagogy. All of them answered the questionnaire Fantastic Lifestyle, composed by 25 questions, subdivided into 9 dimensions: Family and friends (F); Physical activity (PA); Nutrition (N); Tobacco and drugs (TD); Alcohol (Al); Safety, stress and sexual activity (S); Type of behavior (TC); Introspection (I) and Career (C). Each answer assigns a value from 0 to 4 points, totaling a maximum score of 100 (the higher the score, the better the lifestyle). On average, the Business students obtained 65.0 ± 10.4 pts, Pedagogy students reached 67.6 ± 10.9 pts. In the comparison between students of different shifts it was observed that there was no statistical difference (P> 0.05) among students of Pedagogy (Afternoon, n = 56, EVF = 67.8 ± 10.7 pts and Night n=57, EVF 67,4±11,2pts), whereas Business students showed some difference (P=0,01), the morning shift (68.1 ± 9.3) presented better results than the night one (64.1 ± 10.6pts). Finally, it was identified that 35% of Business students reached the minimum score (70 points) considered healthier and of lower risk, with 28 % morning students and 71% night. As for Pedagogy students, 45% obtained EVF considered adequate, being 43% of afternoon and 56% of night. College students’ lifestyle is predominantly inadequate; night students’ lifestyle is worse than day students and this is most evident in male students.